Penerapan Model Kepemimpinan Situasional Menurut Hersey dan Blandhard Pada Lembaga Pendidikan - Atiqoh Atiqoh; Anis Zohriah (Departement of Mathematics Education, 2023)
The author in this study discusses the analysis of situational leadership models looking at the expert opinion of Hersey and Blandhard. According to Hersey and Blanchard there are four situational leadership styles, namely telling, selling, participating, and delegating. Telling is a leadership style that reflects a directing leadership style, this style is loaded with task-oriented behavior and minimal human relations-oriented behavior. This article is a type of qualitative research with a library research approach. In the literature study, the authors carried out activities to collect literature relating to the analysis of situational leadership models. Then a re-examination of the literature is carried out in depth so that it can produce the core of the discussion and conclusions.